Digital Transformation of Inventory Management: Evaluating the Impact of First In First Out-Based Accurate Point of Sale System Implementation on Warehouse Operations - Yulia, Reffa; Seputro, Dimas Nugroho Dwi (International Journal Administration, Business & Organization, 2025)
Every company engaged in manufacturing or distribution requires an effective inventory management system to ensure operational continuity and prevent recording errors. This study aims to evaluate the implementation of a Warehouse Management System based on the Point of Sales (POS) Accurate software using the First In First Out (FIFO) method at PT. Vortex Energy Batam, Giga Energi Teknologi unit. The study employs a mixed-method approach, combining quantitative and qualitative analyses to obtain a comprehensive understanding of the system’s effectiveness. Data were collected through observation, interviews, and literature review. The results show that the implementation of the POS Accurate system with the FIFO method significantly improves recording efficiency, reduces human error, and accelerates stock reporting processes. The average input time per transaction decreased from 10–15 minutes to 3–5 minutes, while data accuracy increased through the system’s automated validation feature. Furthermore, the system enhances integration between departments and improves data transparency. Overall, the implementation of the POS Accurate FIFO-based system effectively strengthens inventory management performance and supports supply chain efficiency.